2008
DOI: 10.1007/s10741-008-9082-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, RAS, and gender: what is the role of aminopeptidases?

Abstract: Hypertension is the major risk factor for coronary heart disease, stroke, and renal disease. Also, it is probably the most important risk factor for peripheral vascular disease and vascular dementia. Although hypertension occurs in both men and women, gender differences have been observed. However, whether sex hormones are responsible for the observed gender-associated differences in arterial blood pressure, and which is their mechanism of action, remains unclear. Local and circulating renin-angiotensin system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 139 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…However, the divergent results imply that the enzyme may be differently regulated in the two conditions and as a function of gender. This phenomenon has already been reported in the case of angiotensinconverting enzymes and proposed as one of the factors which could influence cardiovascular disorders in relation to changes in the renin-angiotensin system [16].…”
Section: Discussionmentioning
confidence: 52%
“…However, the divergent results imply that the enzyme may be differently regulated in the two conditions and as a function of gender. This phenomenon has already been reported in the case of angiotensinconverting enzymes and proposed as one of the factors which could influence cardiovascular disorders in relation to changes in the renin-angiotensin system [16].…”
Section: Discussionmentioning
confidence: 52%
“…The role of CGRP in hypertension is modulated by a number of factors including the reninangiotensin system, steroids, hormones, and so on [40,41], depending on the hypertension model. The notorious sex differences described for these factors in hypertension [42,43] could explain the sex differences observed here. However, other sex-specific genomic, tissue, and cellular characteristics cannot be ruled out in any case [10], and do require further investigation.…”
Section: Discussionmentioning
confidence: 57%
“…This result is consistent with findings from a large cross-sectional study showing increased hypertension among shorter sleeping (<6 h/day) women only (Stranges et al, 2008); as well as the Whitehall II study which reported that shorter sleeping women (≤5 h/day vs. 7 h/day), but not men, had a 19% increased risk of incident hypertension (Cappuccio et al, 2007). Mechanisms are not fully understood, but sex-specific differences in the activity of the angiotensin and renin-angiotensin systems might contribute to poorer control of hypertension in women than in men (Guarner-Lans et al, 2011; Ramírez-Expósito and Martínez-Martos, 2008; Yanes and Reckelhoff, 2011). …”
Section: Discussionmentioning
confidence: 99%